Japan: What to Do with Dead Bodies? A Burning Issue - Crump, Andy (Journal of Institute of Medicine Nepal, 2020)
Death, the passing of a loved one, friend, colleague or just someone we may have known, is virtually always sad and often traumatic. However, it is a part of life and has to be coped with. Each year around 60 million people worldwide die from a wide and diverse number of causes. The problem of what to do with all those dead bodies is becoming a major conundrum for the families involved as well as for policy makers and governments. Natural and anthropogenic disasters, together with increasing incidence of major pandemics of infectious diseases is making finding a solution ever more difficult. A problem which is made worse by ever-increasing draconian rules about what can and cannot be done when disposing of a body.Currently, there are two basic choices, either bury the body in the ground where such action is permitted or cremate it and dispose of the ashes in a culturally and legally acceptable fashion. Generally, both options are becoming prohibitively expensive. The cost of land and the burgeoning demand for land to be used for industry, agriculture, urbanised centres or leisure activities is making burial no longer an option for most people. Japan has long led the world in incineration technology and it has also led the world for many years in cremating its dead. Virtually all Japanese are now cremated, the funeral process involving a mixture of high technology and unique routines steeped in history. Despite widespread concerns that cremation can cause environmental pollution and may damage public health as a result, it is still deemed less polluting than burial. It is likely that countries around the globe will increasingly adopt a policy of cremating their deceased citizens and would do well to follow the lead in this respect being shown by Japan.